Role Of Sponsorship Deal On Sustainability Of Sports Competitions In Kwara State Sports Commission, Nigeria - Memunat Tunrayo Ajadi (UNIVERSITAS NEGERI MAKASSAR, 2024)
Abstract This study investigated the Role of Sponsorship deal on sustainability of Sports Competition in Kwara State Sports Commission, Nigeria. The objective of this study were to: (i) assessed the relationship between marketing strategies and sports competitions (ii) evaluate the relationship between Advertisement and sports competition (iii) examine the relationship between sports finance and sports competition. Descriptive research design of survey type was employed for the study. The population comprises of all sports administrators and coaches in the study area. A multi-stage sampling procedures of stratified and purposive sampling techniques were to select 183 respondents. A researcher structured questionnaire was used to gathered information from the respondent. The instrument was validated by 3 experts in the Department of Human Kinetic Education and tested for reliability through test re-test method using Pearson Product Moment Correlation (PPMC). A correlation coefficient of 0.65r was obtained. The data collected were analysed using percentage and frequency count to analysed the research questions while inferential statistics of Pearson product moment correlation was used to test the postulated hypotheses set for the study at 0.05 alpha level. The result of the finding revealed that there was a significant relationship between marketing strategies, advertisement and sports finance on sustainability of sports competition in Kwara State Sports Commission. Based on the findings, the study therefore recommends that sports administrators should endeavour to partner with private sectors in the area of marketing to the sports competition. Also there is need for sports commission to collaborate with media and companies so as to promote the level of advertisement through sports finance that would enhance smooth organization of sports competition.